Professional Tips and Workarounds for QuickBooks Online - Beetson, Ashley (Packt Publishing, 2021)
Save hours of guesswork and Internet browsing by enhancing your QuickBooks Online skills and leveraging Ash Beetson's extensive QuickBooks knowledge Key Features Broaden your knowledge of QuickBooks Online and accounting concepts Understand how QuickBooks can be adapted to suit different business types using professional techniques Learn best practices for preparing annual accounts before closing the books for the year Book Description Accountants and bookkeepers can sometimes face challenges while coming up with solutions to help their clients. QuickBooks Online, a popular cloud accounting software, comes with a wide range of tools that can take time to learn. This book will show you how to properly combine the tools available in QuickBooks to get the most out of this software. Complete with step-by-step explanations of essential concepts and practical examples, the book will begin by helping you understand how to create opening balances for a new company. You'll then discover essential bookkeeping and accountancy tips and tricks, and find guidance to help make QuickBooks as easy to use as possible. As you advance, you'll explore different scenarios in which QuickBooks Online can be used for various business types. This will help you understand that not every business is the same, but using the wide range of functionalities QuickBooks Online offers, you can customize solutions to really make it work for you. By the end of this QuickBooks book, you'll have gained deep insights into how you can use QuickBooks Online to work for different business types, and you'll have a complete checklist of the different things you should be doing when you start reviewing accounts ahead of tax season. What you will learn Discover how to correctly set up QuickBooks Online with opening balances Adapt QuickBooks Online to meet specific industry needs, from manufacturing and retail using inventory to helping lawyers and property agents handle client funds Get the most out of features such as Projects and Multicurrency Review reports within QuickBooks Online, understand why errors occur, and learn how to resolve them Get to grips with key accounting principles and concepts tailored for bookkeeping and accounting beginners Find out how the audit trail works and explore all of the information it holds Who this book is for Business owners, company directors, accountants, bookkeepers, certified public accountants (CPAs), and anyone studying accounting and bookkeeping ...